Molecular Docking Study of Xanthone Targeting the Dihydropteroate Synthase (2VEG) Enzyme in Streptococcus pneumoniae - Dia Lestari; Resti Aulia Lestari; Alien Putri Hartiwi; Emmy Yuanita; Diah Miftahul Aini (Indonesian Journal of Chemical Science, 2026)
Streptococcus pneumoniae is a pathogenic bacterium causing serious infections, with rising antibiotic resistance highlighting the need for new agents. Dihydropteroate synthase (DHPS) is crucial in bacterial folate biosynthesis and a selective drug target. This study evaluated xanthone derivatives as DHPS inhibitors via molecular docking. Three derivatives namely 1,3,7-trihydroxy-9H-xanthen-9-one (Candidate 1), 1-hydroxy-9-oxo-7-sulfo-9H-xanthene-3-carboxylic acid (Candidate 2), and 9-oxo-1,7-disulfo-9H-xanthene-3-carboxylic acid (Candidate 3), were docked against DHPS (PDB ID: 2VEG) using UCSF Chimera, AutoDock Tools, and AutoDock Vina. Interaction analyses were performed with Discovery Studio and LigPlot+. All candidates bound stably in the DHPS active site; Candidate 2 exhibited the strongest binding (−7.7 kcal/mol) with key hydrogen bonds, while Candidate 3 showed extensive hydrophobic and electrostatic interactions. These results indicate xanthone derivatives, especially Candidate 2, as promising DHPS inhibitors for novel antibacterial development.